DYNAMICS OF THE FORMATION PROCESS OF REGULAR MICRORELIEF ON THE WORKING SURFACES OF CONNECTING ROD BEARINGS - DZYURA, VOLODYMYR; DZHYVAK, TARAS (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents an analysis of the tool performance under conditions of regular microrelief formation on the inner working surface of connecting rod bearings during their machining in a fixture. A mathematical model of the dynamic interaction between the deforming elements of the rotary tool and the micro-irregularities generated by the locks of the connecting rod bearings during the groove formation of regular microreliefs has been developed. It has been established that when the deforming elements come into contact with micro-irregularities, forces arise that induce torsional vibrations of the tool, which affect the groove depth of the formed macrorelief. A differential equation of motion is derived, and the amplitude-frequency characteristics of non-resonant tool vibrations are described. Graphs of the time-dependent amplitude variations of torsional vibrations have been constructed. The analysis of the interaction processes between the micro-irregularities of the internal cylindrical surfaces of connecting rod bearings and the tool’s deforming elements has made it possible to identify its dynamic characteristics. Theoretical investigations have revealed regularities in the occurrence of torsional vibrations of the tool, particularly the conditions for the development of resonant modes. The study provides a detailed comparison between resonant and non-resonant cases and quantitatively assesses the influence of the main parameters — the number and arrangement of balls, diameter, and resonance crossing speed — on vibration amplitude. The novelty of this research lies in identifying specific conditions for the onset of resonant torsional vibrations and in the quantitative comparison of amplitude characteristics of tools with different designs. The findings can be applied to the optimization of tools in order to mitigate the adverse effects of resonance phenomena, thereby improving the accuracy and reliability of machining the surfaces of connecting rod bearings.